Verticalização e tombamento no bairro do Bexiga: materialização em tensão - Scripilliti, Ana Carolina Nader (2017)
Bexiga has a life of its own. It is a central, consolidated and traditional neighborhood of São Paulo city. Located in between the historical center of São Paulo and Paulista Avenue, it is not officially considered a district and since 1910 belongs to Bela Vista. Its origin accompanies the city’s foundation. Shelter of several fugitive slaves and Italian immigrants who had recently arrived at the city, today it is a provisional dwelling for brazilian northeasterners who adopt the neighborhood as a provisional place of residence. Since 2002 the area is considered a preserved heritage site by CONPRESP. It is contemplated as a sample of the urban development process of the history of São Paulo. It was used in this study as an object for the Materialization, understood as the result of the impacts of urbanistic instruments applied over the years. In addition to the transformations that have already taken place, the 2014 Strategic Master Plan proposes axes of urban transformation that can result in major transformations for the neighborhood. The objective of this work is to understand the Materialization of the neighborhood of Bexiga because of the application of urban planning instruments and urban policies, and to expose possibilities of sustainable urban development in areas of preservation and historical patrimony through densification.